The contribution of linguistics to history education - Henríquez, Rodrigo Fernando; Fuentes Cortés, Miguel (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The objective of this article is to review the main contributions of linguistics to the teaching of history and to evaluate its contributions to the ield. More speciically, the themes of historical writing and interactions in the history class will be dealt with. At present, knowledge systems and disciplines are more open to inter- and trans-disciplinary dialog. In this context, linguistics, a science that specializes in language, has permitted the study of how scientiic communities read and write in order to build their knowledge. In the case of history teaching in schools, the contributions of linguistics are varied; among them, the explicit ways in which history is taught and learned through the mediation of language. For this, different references are presented, such as the school of Sydney, Australia; Caroline Cofin, in the United Kingdom; Mary Schleppegrell, in the United Stated, and Teresa Oteíza, Mariana Achugar and the Urdimbre group in Latin America. In reviewing some works by these authors, we provide a panoramic view of some of the focuses that linguistic research in the teaching of history has had in the west to date. It is expected that this article will motivate interdisciplinarity and creativity to employ the language in our history classes.